First Successful Hindcasts of the 2016 Disruption of the Stratospheric Quasi‐biennial Oscillation - S. Watanabe; K. Hamilton; S. Osprey; Y. Kawatani; E. Nishimoto (Geophysical Research Letters)
Abstract In early 2016 the quasi‐biennial oscillation in tropical stratospheric winds was disrupted by an anomalous easterly jet centered at ~40 hPa, a development that was completely missed by all operational extended range weather forecast systems. This event and its predictability are investigated through 40 day ensemble hindcasts using a global model notable for its sophisticated representation of the upper atmosphere. Integrations starting at different times throughout January 2016—just before and during the initial development of the easterly jet—were performed. All integrations simulated the unusual developments in the stratospheric mean wind, despite considerable differences in other aspects of the flow evolution among the ensemble members, notably in the evolution of the winter polar vortex and the day‐to‐day variations in extratropical Rossby waves. Key to prediction of this event is simulating the slowly evolving mean winds in the winter subtropics that provide a waveguide for Rossby waves propagating from the winter hemisphere.